ANALISIS USAHA TANGKAP IKAN TUNA (THUNNUS SP) DENGAN PANCING TONDA DI DESA WAEPURE: (Analysis of the Business of Tuna Catching (Thunnus Sp) With Tonda Fishing in Waepure Village) - Zakariah, Muhammad Ikbal (Uniqbu Journal of Exact Sciences, 2022)
The purpose of this study was to determine the benefits of tuna fishermen with fishing rods in Waepure Village, Air Buaya District, Buru Regency. This research was designed using Data Analysis Method. Data were collected through research instruments in the form of interviews and analyzed using tuna fish business analysis techniques with trolling lines. The results of this study indicate that the benefits of tuna fishermen in Waepure Village, Air Buaya District, Buru Regency are technically profitable and feasible to be developed according to the results. The total profit for the 20 respondent fishermen is Rp. 578,831,000. with the average value of each respondent is Rp. 28,941,550. The average value of the R/C Ratio is 2.73, the BEP value is 5.965 Kg and the average BEP value is 298 Kg. The average value of the Payback Period is 0.58. and the average value of the B/C Ratio is 1.73.